London Transport posters a century of art and design - Bownes, David; Green, Oliver; Black, Jonathan 1969-; Dirix, Emmanuelle; Dobin, Claire; Flood, Catherine; Lewis Bex; Powers, Alan; Rennie ,Paul; Webb, Brian (Lund Humphries In association with London Transport Museum, 2008)
London Transport's poster collection represents the most complete graphic archive of its kind to be assembled by a single organisation over such a long period anywhere in the world. This book is richly illustrated with examples of posters from all periods.